(untitled) (International Seven Journal of Multidisciplinary, 2023)
This article analyzed risk management applied to urban infrastructure projects in the Brazilian public sector, highlighting models, tools and results achieved at different government levels. The research adopted a qualitative approach, with a literature and document review of articles, dissertations and technical guides describing practical experiences in ministries, secretariats and public agencies. The data revealed that the systematic implementation of risk management methodologies promotes higher efficiency, reduces costs and enhances the predictability of schedules and deliveries. Significant advances were identified after the regulation of instruments such as COSO ERM and ISO 31000 adapted to the public sector, enabling the creation of risk matrices, performance indicators and response plans that strengthen governance. Concrete cases were studied, such as the preventive plan of the Civil Defense of Santos, which drastically reduced fatal landslide occurrences, and rail transport projects structured through public private partnerships, in which proper risk allocation increased legal certainty and attractiveness for investors. It was also verified that systems such as ForRisco contributed to institutionalizing risk management in federal institutions by integrating processes and data in digital platforms. Despite the advances, challenges remain related to staff training, resource limitations and the need for an organizational culture focused on prevention. It is concluded that risk management is an essential instrument for sustainable development and the delivery of quality urban infrastructure, promoting greater transparency, efficiency and appreciation of public assets.